Analisa Perbandingan Algoritma DCT, Haar Wavelet, Huffman Dan LZW Pada Kompresi Citra Digital Menggunakan Matlab R2013a - Rahmad Rudi Clinton; Linna Oktaviana Sari (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
Digital image compression is an important method for data transmission and data storage more efficient. There are two compression techniques used are; lossless compression and lossy compression. In lossless compression technique using Huffman and LZW whereas lossy compression technique using the DCT and Wavelet Haar. At any given algorithm image insert 2 input object image is varied according to four dimensions (320x480, 480x640, 640x720, 720x1080) and 4 format (BMP, GIF, PNG and TIFF). the result of applying the algorithm generates the MSE  will be used as a comparison. The result of the application of simulation shows the lossy compression format GIF has the largest MSE of the other formats with MSE value is in the range of 16,4 to 20 dB.    Keywords : Lossy Compression, Lossless Compression, DCT, Haar Wavelet, Huffman, LZW